Strategic innovation and leadership dynamics: Unveiling mediating effects on operational quality in manufacturing organizations - Ricardo Santa; Rodrigo Zarate-Torres; Claudia Fabiola Rey-Sarmiento; Diego Morante (Administrative Sciences, 2025)
This study investigates how strategic innovation influences operational quality, focusing on the mediating effects of transformational and transactional leadership, as well as process innovation, within manufacturing organizations in Colombia. It employs structural equation modeling to analyze data from 180 valid questionnaires. The method allows for an intricate examination of the relationships between strategic innovation and the key organizational variables. The findings reveal that while strategic innovation significantly enhances transactional leadership and process innovation, it does not affect transformational leadership or improve operational quality. This discrepancy with existing literature highlights an urgent need for enhanced leadership development programs that can effectively integrate innovation strategies. This study contributes to the field by delineating specific organizational capabilities and strategies to enhance leadership effectiveness in managing innovation. It underscores the necessity of refining leadership approaches to achieve operational excellence and sustain a competitive edge. The study calls for a more nuanced understanding of how leadership styles can better align with strategic innovation initiatives to improve organizational performance.
Keywords: 350; leadership; operational quality; strategic innovation